Best ideas: avaliação do desempenho de portfólios de ações de alta convicção no mercado brasileiro - Binsfeld, Tiago de Lima (2017)
This paper searches for evidences that equity portfolio managers hold in their portfolios a finite number of stocks able to generate alpha. Theoretical portfolios are built from the best ideas identified in 2.201 Brazilian equity funds in the period from 2009 to 2016. In order to explain the return determinants, we use the five-factor Fama and French model (2015), as well as an alternate six-factor model, with the inclusion of herding. Results indicate that best ideas portfolios presented returns over the IBX 100 portfolio ranging from 0.69% to 2.33% per quarter, while the aggregate of managers’ ideas yielded a return inferior to the benchmark by 0.20% per quarter. By controlling different specifications of the model, alpha was found to be positive and significant at 5% of level of significance.